Ionothermal synthesis, crystal structure, and chemical bonding of the niobium(IV) complex Nb2(Se2)2(AlCl 4)4 - Mueller, Ulrike; Isaeva, Anna; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2014)
The reaction of selenium and NbCl5 with arsenic in the Lewis-acidic ionic liquid BMImCl·4.8AlCl3 at 100°C yielded dark-red block-shaped crystals of Nb2Se4(AlCl 4)4, which immediately decompose when exposed to humid air. Arsenic takes the part of the reducing agent for niobium as well as selenium. The crystal structure was described in the monoclinic space group P21/n (no. 14) with a = 898.0(1) pm, b = 991.3(1) pm, c = 1629.1(2) pm, and β = 92.43(1)° at 296(1) K. The unit cell contains two C 2h symmetric Nb2(Se2)2(AlCl 4)4 molecules. The latter consist of a central rectangular bipyramid [Nb2(Se2)2]4+ and four η2-coordinating AlCl4- tetrahedra. Diamagentism of the compound and DFT-based real-space bonding analysis imply a chemical bond between the niobium(IV) cations, which are 292.2(2) pm apart. Nb2Se4(AlCl4)4 can be interpreted as the AlCl3 adduct of NbSe2Cl2. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Cluster compounds; Ionic liquids; Ionothermal synthesis; Niobium; Selenium